Development and evaluation of an ultraviolet radiation assisted with ohmic heating system for preservation of pineapple juice - DILEEP SEAN, Y; Dr. Prince M. V (Guide) (Tavanur 2015 Department of Food and Agricultural Process Engineering)
ohmic heating is a promising technology
Development and evaluation of an ultraviolet radiation assisted with ohmic heating system for preservation of pineapple juice